2016
DOI: 10.1373/clinchem.2015.251066
|View full text |Cite
|
Sign up to set email alerts
|

The New Substance Abuse and Mental Health Services Administration Oral Fluid Cutoffs for Cocaine and Heroin-Related Analytes Applied to an Addiction Medicine Setting: Important, Unanticipated Findings with LC-MS/MS

Abstract: BACKGROUND:We implemented oral fluid (OF) as an alternative specimen type to urine for detection of cocaine (COC) and opiate abuse in outpatient addiction medicine clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…We conducted a retrospective cohort study of adult patients initiating office-based buprenorphine treatment across a large academic health system based on oral fluid toxicology data between August 2016 and January 31, 2018. Oral fluid toxicology testing was performed using liquid chromatography-tandem mass spectrometry (Flood et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a retrospective cohort study of adult patients initiating office-based buprenorphine treatment across a large academic health system based on oral fluid toxicology data between August 2016 and January 31, 2018. Oral fluid toxicology testing was performed using liquid chromatography-tandem mass spectrometry (Flood et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…We used morphine, codeine, or 6-monoacetylmorphine as a proxy for heroin use because of the short half-life of 6-monoacetylmorphine alone and its rapid metabolism to morphine and codeine. Cutoffs used for a negative test were less than 2.0 ng/mL for 6-monoacetylmorphine (6-MAM) and fentanyl and less than 4.0 ng/mL for codeine and morphine (Flood et al, 2016). We did not examine toxicology outcomes for prescription opioids, including oxycodone, hydromorphone, and hydrocodone, as previous research has demonstrated worse treatment outcomes among individuals using heroin compared to individuals using prescription opioids, thus we would expect that individuals exclusively using prescription opioids would have better treatment outcomes than individuals using fentanyl (Weiss et al, 2015).…”
Section: Study Participantsmentioning
confidence: 99%
“…Our workflow works efficiently in the logP range 0.5 to 5.5. This enables the detection of almost all important illegal drug classes, except cannabinoids, with LOI values that are sufficiently low to fulfill the requirements for screening and confirmation methods issued by regulating authorities, including the Substance Abuse and Mental Health Services Administration (SAMSHA) and the European Workplace Drug Testing Society [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, plasma collection is modestly invasive and requires extensive sensitivity and strong technical reproducibility to overcome the large dynamic range of protein abundance to capture low-abundance biomarkers. The use of oral or salivary fluid is both less invasive and less technically difficult than blood collection, and is susceptible to very rapid turnover in response to physiological processes [11][12][13][14][15]. Measuring biomarkers is unlike the detection of opioid drugs, which is static and drugs can be present for days.…”
Section: Introductionmentioning
confidence: 99%